Questioning Bodies in Shakespeare's Rome Interfacing Science, Literature, and the Humanities / ACUME 2: Volume 4 - Del Sapio Garbero, Maria; Isenberg, Nancy (2010)
Ancient Rome has always been considered a compendium of City and World. In the Renaissance, an era of epistemic fractures, when the clash between the 'new science' (Copernicus, Galileo, Vesalius, Bacon, etcetera) and the authority of ancient texts produced the very notion of modernity, the extended and expanding geography of ancient Rome becomes, for Shakespeare and the Elizabethans, a privileged arena in which to question the nature of bodies and the place they hold in a changing order of the universe. Drawing on the rich scenario provided by Shakespeare's Rome, and adopting an interdisciplinary perspective, the authors of this volume address the way in which the different bodies of the earthly and heavenly spheres are re-mapped in Shakespeare's time and in early modern European culture. More precisely, they investigate the way bodies are fashioned to suit or deconstruct a culturally articulated system of analogies between earth and heaven, microcosm and macrocosm. As a whole, this collection brings to the fore a wide range of issues connected to the Renaissance re-mapping of the world and the human. It should interest not only Shakespeare scholars but all those working on the interaction between sciences and humanities.